Occurrence of salt breakthrough and air-vapor pocket in a direct-contact membrane distillation - Peng, Y.; Ge, J.; Wang, Shaobin; Li, Z. (Elsevier BV, 2017)
© 2016 Elsevier B.V.A polyvinylidene fluoride (PVDF) hollow fiber module with a low packing density and the permeate orifices on one side was used in a direct-contact membrane distillation process (DCMD). Comparative tests were also performed using a highly hydrophobic polytetrafluoroethylene (PTFE) membrane and a low hydrophobic PVDF membrane with different packing densities. Under varying operating conditions such as the feed and permeate flow rates as well as temperature, the performances of the DCMD were comprehensively investigated. It was rarely found that salt breakthrough in an idle mode and air-vapor pocket in an operative mode could occur. Partial wetting was for the first time found tending to happen in the PVDF membrane in idle mode, which led to salt breakthrough. High feed temperature and flow rate accelerated partial wetting. On the contrary, the PTFE membrane prevented partial wetting and blocked salt permeation. The air-vapor pocket formation at the shell side was attributed to a high vapor flux and incomplete condensation. An increase in packing density and the inversion of permeate orifices could help the mixture of hot vapor and cold permeate eliminate the air-vapor pocket, which was for the first time observed and illustrated.